The selectivity of the hair cell’s mechanoelectrical-transduction channel promotes Ca(2+) flux at low Ca(2+) concentrations - Lumpkin, Ellen A. (National Academy of Sciences, 1997)
The mechanoelectrical-transduction channel of the hair cell is permeable to both monovalent and divalent cations. Because Ca(2+) entering through the transduction channel serves as a feedback signal in the adaptation process that sets the channel’s open probability, an understanding of adaptation requires estimation of the magnitude of Ca(2+) influx. To determine the Ca(2+) current through the transduction channel, we measured extracellular receptor currents with transepithelial voltage-clamp recordings while the apical surface of a saccular macula was bathed with solutions containing various concentrations of K(+), Na(+), or Ca(2+). For modest concentrations of a single permeant cation, Ca(2+) carried much more receptor current than did either K(+) or Na(+). For higher cation concentrations, however, the flux of Na(+) or K(+) through the transduction channel exceeded that of Ca(2+). For mixtures of Ca(2+) and monovalent cations, the receptor current displayed an anomalous mole-fraction effect, which indicates that ions interact while traversing the channel’s pore. These results demonstrate not only that the hair cell’s transduction channel is selective for Ca(2+) over monovalent cations but also that Ca(2+) carries substantial current even at low Ca(2+) concentrations. At physiological cation concentrations, Ca(2+) flux through transduction channels can change the local Ca(2+) concentration in stereocilia in a range relevant for the control of adaptation.